Use of short-acting beta agonists in the treatment of asthma across five European countries. Issue 2 (13th January 2022) - Panagiotis, Pavlou; Congleton, Jo
Abstract: Commentary on: Janson C, Menzies-Gow A, Nan C, et al . SABINA: an overview of short-acting β2-agonist use in asthma in European countries. Adv Ther . 2020;37:1124–35. Series co-ordinator: Dr Teck Khong, DTB Associate Editor Clinical Pharmacology, St George's, University of London, UK